HUBUNGAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLING FUTSAL SISWA KELAS X E1 SMA NEGERI 12 KOTA JAMBI - Reynaldi Silaban; Yahdil Yahmin; Muhammad Aqil Alfaruq; Ely Yuliawan; Mohd. Adrizal; Vito Ardiva Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study employed a quantitative method with a correlational research design. The study population consisted of 30 students who participated in futsal activities at SMA Negeri 12, and all members of the population were included as the sample using the total sampling technique. Agility was measured using the Illinois Agility Test, while dribbling ability was assessed through a futsal dribbling test. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Spearman Rank correlation test with the assistance of SPSS software. The results showed a Spearman Rank correlation coefficient of 0.584 with a significance value of < 0.001. These findings indicate a positive and significant relationship between agility and futsal dribbling ability. The correlation coefficient, which falls within the moderate category, suggests that improvements in agility tend to be accompanied by improvements in students’ dribbling ability. In other words, students with higher levels of agility generally demonstrate more effective dribbling performance. Based on these findings, it can be concluded that agility has a significant relationship with futsal dribbling ability among students of SMA Negeri 12. Therefore, coaches and physical education teachers are encouraged to design training programs that focus on improving agility in order to support the development of dribbling skills and overall futsal performance.